Hyperspectral monitoring of wheat gluten index based on multi-model ensemble and adaptive learning - Shiyou Zhu; Juan Bai; Yulong Chen; Jingyu Chen; Caiyu Ji; Yingchao Hao; Sha Yang; Yu Zhao; Meijun Zhang; Meichen Feng; Wude Yang; Guangxin Li (Food Chemistry, 2026)

Metal-node coupling of triboelectricity in conductive metal–organic frameworks for contact-electro-catalytic H2O2 generation - Meichen Li; Shuqi Zhou; Yinben Guo; Xueshuang Xiao; Qiqing Xi; Ximing Wang; Xin Han; Qiang Yang (Chemical Engineering Journal, 2026)

Iron-regulated crystallization in sensible-heat-driven glass-ceramics from molten lead-zinc smelting slag: Process-structure-property coupling and LCA quantification - Yibo Yang; Yusheng Tang; Hanguang Fu; Mengchen Xiao; Meichen Pan; Jixian Wu; Zhichuan Li; Zhe Tan; Zhixue Qu; Dean Pan; Xiaoguang Zhang (Process Safety and Environmental Protection, 2026)

Unveiling the landscape of BPS derivatives in urine from eastern and western Chinese population - Qingqing Zhu; Meichen Lu; Xueyu Weng; Yitong Pan; Xianping Wei; Longyao Xu; Yifan Li; Chunyang Liao; Guibin Jiang (Environmental Research, 2026)

Flavonoids from the heartwood of Cotinus coggygria Scop. (Anacardiaceae) and their chemophenetic significance - Hongyun Bai; Caiwen Meng; Wenjing Zu; MeiChen Li (Biochemical Systematics and Ecology, 2026)

Machine learning with augmented data for predicting bentonite swelling pressure - Wenyan Shi; Feng Zhang; Changdong Li; Qingbing Liu; Long Xu; Zhangrong Liu; Hangjing Zhou; Meichen Liu; Yuxian Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Corrigendum to “Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics” [Food Chem. 513 (2026) 149020] - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Rapid fractionation of moso bamboo using ternary deep eutectic solvent for integrated enzymatic hydrolysis and in situ treatment liquid gelation - Jiaying Li; Chengcheng Yuan; Meichen Zhang; Yingchao Wang; Feng Xu; Fengshan Zhang; Zongwei Guo; Hao Ma; Xingxiang Ji (Chemical Engineering Journal, 2026)

Spatiotemporal heterogeneity of carbon balance effects in China's population-shrinking cities amid urban transition - Jianwen Zhang; Meichen Fu; Yanqing Liang; Chaoran Zhao; Sijia Li; Feng Tang (Applied Geography, 2026)

Decoupling of arbuscular mycorrhizal fungi and soil organic carbon under nitrogen addition in terrestrial ecosystems: a meta-analysis - Andi Li; Jing Chen; Senhao Wang; Guangcan Yu; Meichen Xu; Anchi Wu; Jinhua Mao; Wei Zhang; Zhanfeng Liu; Juxiu Liu; Jiangming Mo; Mianhai Zheng (Frontiers of Earth Science, 2026)

Key antioxidant compounds and potential mechanisms in Peckorumyces umbonatus solid-state fermented grains: An integrated metabolomics, network pharmacology, and molecular docking study - Meichen Pan; Jipeng Li; Changtian Li; Yueting Dai (Food Bioscience, 2026)

Hyperspectral estimation on the photosynthetic phenotype of winter wheat under drought stress using machine learning algorithms - Yanxia Chen; Xiaobin Yan; Tingyue Huo; Yuchao Yang; Bei Tie; Chenhao Qin; Meichen Feng; Xingxing Qiao; Xiaokai Chen; Guangxin Li; Chao Wang; Wude Yang (Precision Agriculture, 2026)

Microalgae-bacteria interactions in acidic mining pit lakes: Community assembly and environmental drivers - Meichen Wang; Jin Wang; Xin Pan; Zijie Yu; Ziyi Li; Rui Deng; Zhengbo Yue (Process Safety and Environmental Protection, 2026)

Regulating mineral ions to enhance uranium phytoremediation by Macleaya cordata under synergistic effects of oxalic acid and Fusarium sp. A-2 - Meichen Li; Huang Yu; Tao Lang; Qinwen Deng; Weichao Zhao; Hui Zhang; Yuan Xue; Yongdong Wang; Dexin Ding; Nan Hu (Journal of Environmental Radioactivity, 2026)

Synergistic enhancement of phytoremediation efficiency and mechanisms of uranium-contaminated soil by oxalic acid and endophytic fungus Fusariumsp. A-2 withMacleaya cordata - Kongjun Zhu; Zhaolan Yang; Meichen Li; Qinwen Deng; Fangfang Xiao; Yongdong Wang; Dexin Ding; Huang Yu; Nan Hu (Journal of Environmental Radioactivity, 2026)

Chemical constituents from the fruits of Toxicodendron vernicifluum (Stokes) F. A. Barkley (Anacardiaceae) and their chemotaxonomic significance - Wenjing Zu; Lu Guan; Jie Liu; Cai-Wen Meng; Hongyun Bai; MeiChen Li; Jianyu Liu; Yongnan Xu (Biochemical Systematics and Ecology, 2026)

Integrating leaf-scaled spectra and machine learning for rapid estimation of photosynthetic phenotypes across soybean genotypes - Chao Wang; Xiaobin Yan; Yan Bai; Jiaxue Zhang; Xinhui Guo; Xiaomei Zhang; Meichen Feng; William Rickard; Yu Zhao; Fangzhou Li; Chenbo Yang; Xiaokai Chen; et al. (Computers and Electronics in Agriculture, 2025)

Small lakes, big improvements: a multi-decadal assessment of policy and climate impacts on chlorophyll-a in China - Sijia Li; Hong Yang; Ge Liu; Dehua Mao; Zongming Wang; Haiqing Liao; Lele Zhang; Haoyun Zhou; Meichen Ji; Kaishan Song (Science Bulletin, 2025)

Monitoring the growth status of winter wheat by using the machine learning algorithm and the fusion of spectral and texture features derived from the UAV remote sensing - YiMing Su; XiaoBin Yan; Hao Li; ZiHao Liang; ShuangMei Zhao; Ping Chen; Zhen Zhang; XingXing Qiao; Yu Zhao; MeiChen Feng; Fahad Shafiq; XiaoYan Song; et al. (Computers and Electronics in Agriculture, 2025)

Microwave heating:A new high efficiency and low energy-consumption option for removing PFOA and PFOS from soil - Meichen Yao; Jialun Shen; Huan Yang; Xiaodong Li; Fujun Ma; Qingbao Gu (Journal of Environmental Management, 2025)

An integrated CFD and CNN-GRU approach for accurate prediction of PM2.5 in greenhouse environments of Northeast China - Shuo Zhang; Li Guo; Haiye Yu; Bo Zhang; Meichen Chen; Lei Zhang; Dawei Li; Yuanyuan Sui (Building and Environment, 2025)

Plant morphological and physiological traits are stable in a nitrogen-saturated tropical forest after 18-year nitrogen additions - Guangcan Yu; Jing Chen; Andi Li; Senhao Wang; Liang Song; Xianmeng Shi; Junhua Yan; Meichen Xu; Yuewei Xue; Xiankai Lu; Wei Zhang; Juan Huang; et al. (Plant and Soil, 2025)

Comparative analysis of the effects of different dimensionality reduction algorithms on hyperspectral estimation of total nitrogen content in wheat soils - Juan Bai; Shiyou Zhu; Yingchao Hao; Xinzhe Li; Chenbo Yang; Chao Wang; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Sha Yang; et al. (European Journal of Agronomy, 2025)

A UAV-based hybrid approach for improving aboveground dry biomass estimation of winter wheat - Yu Zhao; Haikuan Feng; Shaoyu Han; Chao Wang; Meichen Feng; Lujie Xiao; Zhenhai Li; Wude Yang; Guijun Yang (European Journal of Agronomy, 2025)

Magnetic properties of agricultural soils and their relationships with environmental factors in Jinghong, Yunnan, China - Meichen Wang; Haixia Li; Shiyu Li; Yudong Chen; Gangqiang Li (Earth Science Informatics, 2025)

Seasonal variation drives species coexistence and community succession in microbial communities of stratified acidic pit lakes - Meichen Wang; Xin Pan; Zhengbo Yue; Rui Deng; Ziyi Li; Jin Wang (Journal of Environmental Management, 2025)

Quercetin attenuates DEHP-induced pyroptosis and programmed necrosis in chicken duodenum through regulation of the TLR4/MyD88/NF-κB pathway - Ruirui Xie; Tong Xu; Yilin Yin; Meichen Liu; Chenxi Huang; Wenwen Zhang; Shu Li (Environmental Pollution, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Mechanism of decolorization and degradation of direct brown D3G by a halo-thermophilic consortium - Wenying Wang; Zuotao Zhang; Meichen Sun; Chenlai Li; Mengdi Yan; Chongyang Wang (Extremophiles, 2025)

Radiomics-based Modelling Unveils Cerebellar Involvement in Parkinson’s Disease - Yini Chen; Yiwei Qi; Yiying Hu; Tao Qiu; Meichen Liu; Qiqi Jia; Yubing Sun; Xinhui Qiu; Bo Sun; Zhanhua Liang; Weidong Le; Tianbai Li (The Cerebellum, 2025)

Serum arsenic augments gallstone risk in Henan rural cohort with multiple metal exposure - Qian Zhang; Yating Li; Han Hu; Meichen Tian; Tingting Cao; Hui Wu; Weidong Wu; Guofu Zhang (Science of The Total Environment, 2024)

Photolysis of p-phenylenediamine rubber antioxidants in aqueous environment: Kinetics, pathways and their photo-induced toxicity - Chen Wang; Meichen Sun; Minghui He; Siyu Zhao; Meinuo Lv; Xiaotian Xu; Chunbei Ye; Linjing Li; Limin Su; Yuanhui Zhao (Journal of Hazardous Materials, 2024)

Silicon dioxide particles induce DNA oxidative damage activating the AIM2-mediated PANoptosis in mice cerebellum - Hao Cai; Meichen Gao; Tong Xu; Ke Li; Yuanxin Zhou; Chencong Lyu; Shiwen Xu (Chemico-Biological Interactions, 2024)

Changes in the magnetic properties of a tropical red soil following the conversion of forest into agricultural land - Meichen Wang; Fengrui Li; Haixia Li; Xiaoling Zhang; Shiyu Li; Gangqiang Li; Yudong Chen; Yang Wang; Jingyuan Hu; Junmin Ye (Journal of Applied Geophysics, 2024)

Dietary bile acids inclusion improves dietary carbohydrate utilization, antioxidant capacity and intestinal microbiota and inflammation of largemouth bass (Micropterus salmoides) - Wenfei Li; Ye Gong; Ning Liu; Shiwen Chen; Meichen Yue; Jinbao Li; Xuxiong Huang; Naisong Chen; Songlin Li (Aquaculture, 2024)

Combined use of spectral resampling and machine learning algorithms to estimate soybean leaf chlorophyll - Chunrui Gao; Hao Li; Jiachen Wang; Xin Zhang; Kunming Huang; Xiaoyan Song; Wude Yang; Meichen Feng; Lujie Xiao; Yu Zhao; Fahad Shafiq; Chao Wang; et al. (Computers and Electronics in Agriculture, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Efficient prediction of SOC and aggregate OC components by continuous wavelet transform spectra under different feature selection methods - Sha Yang; Zhigang Wang; Caiyu Ji; Yingchao Hao; Zihao Liang; Xiaobin Yan; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Guangxin Li; et al. (Computers and Electronics in Agriculture, 2024)

Long‐term nitrogen and phosphorus addition have stronger negative effects on microbial residual carbon in subsoils than topsoils in subtropical forests - Linjie Fan; Yuewei Xue; Donghai Wu; Meichen Xu; Andi Li; Baixin Zhang; Jiangming Mo; Mianhai Zheng (Global Change Biology, 2024)
Highly weathered lowland (sub)tropical forests are widely recognized as nitrogen (N)‐rich and phosphorus (P)‐poor, and the input of N and P affects soil carbon (C) cycling and storage in these ecosystems. Microbial residual C (MRC) plays a crucial role in regulating soil organic C (SOC) stability in forest soils. However, the effects of long‐term N and P addition on soil MRC across different soil layers remain unclear. This study conducted a 12‐year N and P addition experiment in two typical subtropical plantation forests dominated by Acacia auriculiformis and Eucalyptus urophylla trees, respectively. We measured plant C input (fine root biomass, fine root C, and litter C), microbial community structure, enzyme activity (C/N/P‐cycling enzymes), mineral properties, and MRC. Our results showed that continuous P addition reduced MRC in the subsoil (20–40 cm) of both plantations ( A. auriculiformis : 28.44% and E. urophylla : 28.29%), whereas no significant changes occurred in the topsoil (0–20 cm). N addition decreased MRC in the subsoil of E. urophylla (25.44%), but had no significant effects on A. auriculiformis . Combined N and P addition reduced MRC (34.63%) in the subsoil of A. auriculiformis but not in that of E. urophylla . The factors regulating MRC varied across soil layers. In the topsoil (0–10 cm), plant C input (the relative contributions to the total variance was 20%, hereafter) and mineral protection (47.2%) were dominant factors. In the soil layer of 10–20 cm, both microbial characteristics (41.3%) and mineral protection (32.3%) had substantial effects, whereas the deeper layer (20–40 cm) was predominantly regulated by microbial characteristics (37.9%) and mineral protection (18.8%). Understanding differential drivers of MRC across soil depth, particularly in deeper soil layers, is crucial for accurately predicting the stability and storage of SOC and its responses to chronic N enrichment and/or increased P limitation in (sub)tropical forests.

Trade-off and driving factors of water-energy-food nexus in Mu Us sandy land, China - Shuxin Mao; Jiawei Lv; Meichen Li; Lei Li; Jian Xue (Journal of Cleaner Production, 2024)

Structural and mineralogical variation upon reoxidation of reduced Fe-bearing clay minerals during thermal activation - Wenwen Zhang; Xiaodong Li; Yao Zhao; Zongquan Sun; Meichen Yao; Xuefei Zhou; Fasheng Li; Fujun Ma; Qingbao Gu (Science of The Total Environment, 2023)

Trimethyltin chloride induces apoptosis and DNA damage via ROS/NF-κB in grass carp liver cells causing immune dysfunction - Lulu Li; Meichen Gao; Naixi Yang; Liwen Ai; Liyang Guo; Xuexue Xue; Zunlai Sheng (Fish & Shellfish Immunology, 2023)

Efficient antibiotic wastewater treatment via interfacial water evaporation based soot-coated conjugated microporous polymer hollow microspheres - Wenwen Luo; Meichen Liu; Rui Jiao; Yunjia Wang; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Hanxue Sun; An Li (Chemical Engineering Journal, 2023)

A new flavonoid glycoside from Toxicodendron vernicifluum (Stokes) F.A. Barkley - Chengye Zhao; Meichen Li; Yuqian Yang; Minni Qin; Ruojia Wang; Qing Zhu; Guangtong Chen; Andong Wang (Natural Product Research, 2023)

Optimization of SbBix nanoparticles embedded in ultra-thin carbon networks for enhanced sodium/potassium storage - Qingxin Lin; Jian Qin; Yanyan Cao; Xiaokang Li; Yan Hong; Meichen Jin; Jinjuan Dong; Wei Xiao; Wenbin Li; Jingjing Wang; Xifei Li (Chemical Engineering Journal, 2023)

Negative responses of terrestrial nitrogen fixation to nitrogen addition weaken across increased soil organic carbon levels - Mianhai Zheng; Meichen Xu; Dejun Li; Qi Deng; Jiangming Mo (Science of The Total Environment, 2023)

Formation Control for Mixed-Order UAVs–USVs–UUVs Systems under Cooperative and Optimal Control - Meichen Liu; Yandong Li; Ling Zhu; Yuan Guo; Bohao Liu (Journal of Marine Science and Engineering, 2023)
In this paper, cooperative control and optimal control methods are used for the formation control of mixed-order heterogeneous multi-agent systems. The system consists of unmanned aerial vehicles (UAVs), unmanned surface vehicles (USVs), and unmanned underwater vehicles (UUVs). The system is represented in a state space using a block Kronecker product. The static and dynamic formation control protocols are proposed respectively, and the graph theory is used to prove that formation control protocols can realize system formation. Furthermore, the optimal control and cooperative control are introduced into the static and the dynamic formation control protocols, and the static cooperative optimal formation control protocol and the dynamic cooperative optimal formation control protocol are designed. Through MATLAB simulation, the static cooperative optimal control protocol and static formation control protocol are compared, and the dynamic cooperative optimal control protocol and dynamic formation control protocol are compared. By comparison, the state variables of the system can reach convergence quickly, and the system can complete formation in a short time, which verifies the effectiveness of the optimal theory and cooperative control.

Identification of structural variations related to drought tolerance in wheat (Triticum aestivum L.) - Jiajia Zhao; Xiaohua Li; Ling Qiao; Xingwei Zheng; Bangbang Wu; Meijun Guo; Meichen Feng; Zengjun Qi; Wude Yang; Jun Zheng (Theoretical and Applied Genetics, 2023)

Evaluation of data pre-processing and regression models for precise estimation of soil organic carbon using Vis–NIR spectroscopy - Yaxin Wang; Sha Yang; Xiaobin Yan; Chenbo Yang; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Fahad Shafiq; Hui Sun; Guangxin Li; Wude Yang; et al. (Journal of Soils and Sediments, 2023)

Verniciflavanol A, a profisetinidin-type-4-arylflavan-3-ol from toxicodendron vernicifluum protects SH-SY5Y cells against H2O2-Induced oxidative stress - Meichen Li; Yunqiang Zhang; Tingting Han; Lu Guan; Dongxue Fan; Qinke Wu; Jianyu Liu; Yongnan Xu; Yanhua Fan (Phytochemistry, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

ROS/ER stress contributes to trimethyltin chloride-mediated hepatotoxicity; Tea polyphenols alleviate apoptosis and immunosuppression - Huijun Zhu; Meichen Gao; Wenying Sun; Huanyi Liu; Shiwen Xu; Xiaojing Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Isolation of a new monoterpenoid glycoside from Anhua dark tea based on an NMR-guided method and its cytotoxic activity against MDA-MB-231 and SH-SY5Y cell lines - Yunqiang Zhang; Jianyu Liu; Miao Chen; Yanhua Fan; Meichen Li; Andong Wang; Gaigai Liu; Yongnan Xu; Xuhong Ren; Yan Xiao (Natural Product Research, 2022)

Dlg1 Knockout Inhibits Microglial Activation and Alleviates Lipopolysaccharide-Induced Depression-Like Behavior in Mice - Zhixin Peng; Xiaoheng Li; Jun Li; Yuan Dong; Yuhao Gao; Yajin Liao; Meichen Yan; Zengqiang Yuan; Jinbo Cheng (Neuroscience Bulletin, 2021)
Microglia-mediated neuroinflammation is widely perceived as a contributor to numerous neurological diseases and mental disorders including depression. Discs large homolog 1 (Dlg1), an adaptor protein, regulates cell polarization and the function of K + channels, which are reported to regulate the activation of microglia. However, little is known about the role of Dlg1 in microglia and the maintenance of central nervous system homeostasis. In this study, we found that Dlg1 knockdown suppressed lipopolysaccharide (LPS)-induced inflammation by down-regulating the activation of nuclear factor-κB signaling and the mitogen-activated protein kinase pathway in microglia. Moreover, using an inducible Dlg1 microglia-specific knockout ( Dlg1 flox/flox ; CX3CR1 CreER ) mouse line, we found that microglial Dlg1 knockout reduced the activation of microglia and alleviated the LPS-induced depression-like behavior. In summary, our results demonstrated that Dlg1 plays a critical role in microglial activation and thus provides a potential therapeutic target for the clinical treatment of depression.

A novel defensin-like peptide contributing to antimicrobial and antioxidant capacity of the tick Dermacentor silvarum (Acari: Ixodidae) - Fengjiao Li; Zhihua Gao; Kuang Wang; Yinan Zhao; Hui Wang; Meichen Zhao; Yawen Zhao; Lingqian Bai; Zhijun Yu; Xiaolong Yang (Experimental and Applied Acarology, 2021)

Risks Assessment Associated with Different Sources of Metals in Abandoned Soil of Zhuxianzhuang Coal Mine, Huaibei Coalfield (Anhui, China) - Hongxia Fang; Herong Gui; Jun Li; Hao Yu; Meichen Wang; Yaqi Jiang; Chunlei Wang; Chen Chen; Yaru Zhang; Yiheng Huang (Bulletin of Environmental Contamination and Toxicology, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

An integrated system for rapid assessment of ecological quality based on remote sensing data - Qian Ding; Li Wang; Meichen Fu; Ni Huang (Environmental Science and Pollution Research, 2020)

Occurrence and distribution of selected antibiotics in the surface waters and ecological risk assessment based on the theory of natural disaster - Sijia Li; Hanyu Ju; Jiquan Zhang; Peng Chen; Meichen Ji; Jianhua Ren; Shuyun Zhao (Environmental Science and Pollution Research, 2019)

Evaluation of CDOM sources and their links with antibiotics in the rivers dividing China and North Korea using fluorescence spectroscopy - Guangyi Mu; Meichen Ji; Sijia Li (Environmental Science and Pollution Research, 2018)

The relationship of chromophoric dissolved organic matter parallel factor analysis fluorescence and polycyclic aromatic hydrocarbons in natural surface waters - Sijia Li; Ya’nan Chen; Jiquan Zhang; Kaishan Song; Guangyi Mu; Caiyun Sun; Hanyu Ju; Meichen Ji (Environmental Science and Pollution Research, 2018)

De novo characterization of the antler tip of Chinese Sika deer transcriptome and analysis of gene expression related to rapid growth - Baojin Yao; Yu Zhao; Qun Wang; Mei Zhang; Meichen Liu; Hailong Liu; Juan Li (Molecular and Cellular Biochemistry, 2012)

Sequencing and de novo analysis of the Chinese Sika deer antler-tip transcriptome during the ossification stage using Illumina RNA-Seq technology - Baojin Yao; Yu Zhao; Haishan Zhang; Mei Zhang; Meichen Liu; Hailong Liu; Juan Li (Biotechnology Letters, 2012)